Indicators and Manifestations of the Balancing between International Carriage Parties according to the Rotterdam Rules - Al-Houthi, Abdullah Yahya Mohammed (Journal of Economic, Administrative and Legal Sciences, 2023)
The regulations and rules governing maritime transport were not uniform among countries. Such uniformity is due to a failure to accede to a single convention. Countries were either acceded to or withdrawn from the Brussels Convention, and acceded instead to the Hamburg Convention, and so on. As a consequence, international maritime transport provisions no longer have the status of legal unification, making international commercial transactions unstable, in addition to the development in international trade and maritime transport in particular, such as reliance on containerized transport, use of technology in Multimodal transportation and consideration of door-to-door transport as a phase of maritime transport. In response, the United Nations Commission on International Trade Law (UNCITRAL) undertook to prepare a new draft convention on contracts for the international carriage of goods wholly or partly by sea ("Rotterdam Rules"), which was adopted on 11 December 2008. The texts of that Convention are international substantive rules concluded within the framework of an international organization (United Nations), representing a binding and acceptable global regulation, which contain solutions compatible with the relevant international treaties and a balance of the responsibilities and obligations of all parties (carrier and shipper) engaged in the international carriage of goods and associated third parties, And this balance was brought by the rules with many indicators in their rulings that indicated it which govern all different modes of transport as one contract. This is what the study deals with by presentation and analysis, leading to the confirmed results.
Keywords: Rotterdam Rules; Transport Parties and Their Responsibilities; Initial; basic; objective balance indicators